KRITIK WAYANG KEMPLO TERHADAP DUNIA PENDIDIKAN DI PONOROGO - Nurul Iman (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
Puppet (Wayang) in its development has been used as media of entertainment, show, preaching, illumination, even social criticism. At Ponorogo, there was Wayang Kemplo which writes and tells stories of puppet figures in accordance with the local area reality and considered as a feedback or criticism towards some social realities, based on self anxiety of its puppeteer. This paper will examine the criticism of Wayang Kemplo againts the social dynamic of Ponorogo, particularly on the education and the academic society response towards these criticism. Among those things that can be summed up by this study, are: (1) Society, the education world in particular is a community that is supposed to be familiar with valuas such as honesty, hard working, discipline, etc. however, it showed that the reallity was as its opposite. Academic community often showed lies, laziness, and lack of discipline through purchasing the academic degree, cheating culture, or false scientific work. Those reality caused corcern of the puppeteer to criticize them through his wayang kemplo, (2) The criticism of wayang kemplo was responded differently, some took it seriously and even tried to intimidate the author, mainly the criticized officials. Many also thought of it as an entertainment for its humor and jokes, so the presence of these posts were always eagerly anticipated.